Husbandry and Herding: A Community-Based Approach to Addressing Illegal Wildlife Trade in Northern Botswana - Heermans, Ben; van Rooyen, Jacques; Fynn, Richard; Biggs, Duan; Lewis, Matthew; McNutt, John (Frontiers in Conservation Science, 2021)
Illegal bushmeat hunting is a major driver of wildlife population declines in Northern Botswana. Such declines raise concerns about the principles and integrity of the Kavango-Zambezi Transfrontier Conservation Area (KAZA) and regional economic stability which is heavily reliant on wildlife-based tourism. The KAZA landscape between Northern Botswana’s protected areas consists of non-state land utilized communally by small agropastoralist communities. These communities are economically challenged by international beef trade policies, restricted access to grazing in nearby wildlife management areas and high conflict costs from living in close proximity to wildlife; some of the key factors identified as drivers of bushmeat hunting in the region. Here we describe how a model called Herding for Health (H4H) could address these drivers. We discuss strategies using a socio-economic centered Theory of Change (ToC) model to identify the role agropastoral communities can have in addressing illegal wildlife trade (IWT). The ToC conceptual framework was developed with input from a resource team consisting of scientific and implementation experts in H4H, wildlife conservation, illegal wildlife trade and livelihood development between September and December 2018, and with a validation workshop in March 2019 with government representatives from relevant ministries, NGO’s, community-based organizations and private sector participants. We identify three pathways deriving from the ToC driven by community level actions to address IWT in the region. These include: increasing institutions for local enforcement, developing incentives for ecosystem stewardship and decreasing the costs of living alongside wildlife. The success of these pathways depends on underlying enabling actions: support for the development of institutional frameworks; building community capacity to facilitate informed best farming practices; and strengthening commitments to sustainable resource management to increase resilience to climatic and economic shocks.